A particle swarm optimization algorithm for the multiple-level warehouse layout design problem - Onut, Semih; Tuzkaya, Umut R.; Dogac, Bilgehan (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Warehouse operation and management is one of the essential parts of manufacturing and service operations. The warehouse layout problem is a key to warehouse operations. Generally, warehouse layout design models attempt to optimize different objectives such as the orientation of storage racks, the allocation of space among competing uses, the number of cranes, the overall configuration of the facility, etc. The warehousing strategies can be classified as distribution-type, production-type and contract-type warehouse strategies. In this study, a distribution-type warehouse considered that various type products are collected from different suppliers for storing in the warehouse for a determined period and for delivery to different Customers. The aim of the Study is to design a multiple-level warehouse shelf configuration which minimizes the annual carrying costs. The turnover rates of the products are classified and they are considered while putting/picking them to/from shelves regarding the distances between the shelves and docks. Since proposed mathematical model was shown to be NP-hard, a particle swarm optimization algorithm (PSO) as a novel heuristic was developed for determining the optimal layout. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: warehouse layout; order-picking; class-based storage; particle swarm optimization; GENETIC ALGORITHMS; ASSIGNMENT; ALLOCATION; LOCATION; SYSTEM; PSO; Computer Science; Engineering